2003
DOI: 10.1002/tea.10082
|View full text |Cite
|
Sign up to set email alerts
|

Intervention program to keep girls in the science pipeline: Outcome differences by ethnic status

Abstract: This study evaluated a 2-week residential program aimed at enhancing the science interest and persistence of high-achieving 8th-grade girls. Questionnaires were administered to 38 program participants (14 of whom were of minority ethnicity) and 173 applicants who did not attend the program, at 3 time points: preprogram, 1 year postprogram, and 4 years postprogram. Outcomes, measured postprogram, included science self-concept and interest, persistence and aspirations in science, science activities, science cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 27 publications
0
32
1
1
Order By: Relevance
“…Despite the small effect size (see Cohen, 1988) of CBEPs on attitudes, the results can still be regarded as educationally significant, noting that small effect sizes on attitudes are common for studies involving science enrichment programmes. The effect size detected in this study was greater than those reported in a likewise short-term study (see for example; Jarvis & Pell, 2005) or was on par, if not greater, than those of studies that focused on relatively longer enrichment programmes (Falk & Balling, 1982;Jayaratne, Thomas, & Trautmann, 2003) held in out-of-school settings. It is also worth noting that a sizeable percentage (at least 20%) of the participants reported retention of considerable attitude gains (10% or three-point increase in subscale scores) 2 weeks post-CBEP.…”
Section: Affective and Cognitive Resultscontrasting
confidence: 79%
“…Despite the small effect size (see Cohen, 1988) of CBEPs on attitudes, the results can still be regarded as educationally significant, noting that small effect sizes on attitudes are common for studies involving science enrichment programmes. The effect size detected in this study was greater than those reported in a likewise short-term study (see for example; Jarvis & Pell, 2005) or was on par, if not greater, than those of studies that focused on relatively longer enrichment programmes (Falk & Balling, 1982;Jayaratne, Thomas, & Trautmann, 2003) held in out-of-school settings. It is also worth noting that a sizeable percentage (at least 20%) of the participants reported retention of considerable attitude gains (10% or three-point increase in subscale scores) 2 weeks post-CBEP.…”
Section: Affective and Cognitive Resultscontrasting
confidence: 79%
“…The results of these programs that use an inquiry approach have been mixed, with many showing a positive impact on girls' science attitudes and long-term career choices (Baker 2013;Brickhouse et al 2000;Fadigan and Hammrich 2004;Jovanivich and King 1998;Kahle and Damnjanovic 1994;Mattern and Schau 2002;Palmer 2009;Stake and Mares 2001), as well as some neutral outcomes (Carlone 2004;Davis 2002;Jayaratne et al 2003; BaramTsabari et al 2009). Given that inquiry-based learning has produced some promising results, it is critical that educators come to better understand how this approach can improve girls' science attitudes and content knowledge.…”
Section: Introductionmentioning
confidence: 95%
“…25 To simultaneously address both of these issues: the persistent gender gap in STEM disciplines and the lack of hands-on science education, we developed a full-time, week-60 long chemistry camp for middle school girls in Rhode Island. Hands-on full-time outreach programs for girls have previously been reported by this 34 and other journals; [35][36][37] review articles on this topic have also been published. 38 Only one of the previously reported full time programs was focused on chemistry, and in that case focused particularly on analytical chemistry experiments.…”
mentioning
confidence: 99%